IMMU-49. THE SELECTIVE ENRICHMENT OF T CELLS TARGETING UNKNOWN BRAIN CANCER ANTIGENS VIA TROGOCYTOSIS. (11th November 2019) - Moore, Ginger; Divita, Bayli; Flores, Catherine; Mitchell, Duane
Abstract: INTRODUCTION: Trogocytosis is the exchange of membrane components from one cell to another. During T cell activation, dendritic cell (DC) and T cell membranes become anchored around the TCR/MHC complex and their costimulatory molecules. Part of the DC membrane is pulled away, taken in, and educates the T cell to recognize foreign antigens. We have utilized this phenomenon to isolate and expand a select population of T cells that have undergone this interaction. HYPOTHESIS: (1) By selecting for cells that have undergone trogocytosis, we are enriching for a tumor-specific population of T cells and can improve anti-tumor responses in the setting of adoptive cellular transfer (ACT). (2) This approach represents a reliable method to detect tumor-specific antigens across numerous types of brain cancers. METHODS: Murine DCs are pulsed with KR158B glioma RNA and then stained with a proliferation dye such as Cell Trace Violet. These cells are co-cultured overnight with CD3+ splenocytes of vaccinated mice and IL-2. The cells are then sorted into T cells that have undergone trogocytosis (CD3+ CTV+) and those that have not (CD3+CTV-) and placed back into co-culture with fresh dendritic cells for expansion of tumor-specific T cells and/or restimulation assay. Additionally, T cells are spectratyped and phenotyped by flow cytometry. RESULTS: Cells that had undergone trogocytosis (CD3+CTV+) demonstrated superior IFNγ secretion and enriched for CD4+ and CD8+ central memory and effector subsets compared to cells that had not undergone trogocytosis (CD3+CTV-). Spectratyping analysis revealed CD3+CTV+ cells enriched for Vβ 5.1/5.2 and Vβ 6, two families we have determined to be crucial for anti-tumor efficacy. CONCLUSIONS: This method of selection and enrichment of tumor-specific T cells has promising implications for the enhancement of ACT. This method can be used to elucidate tumor-specific antigens that are unique to an individual's cancer fingerprint.